From sub-IDOs to Impact: A Guide to Developing Gender-related Policy Indicators in CCAFS - Tavenner, Katie; Cramer, Laura K.; Thornton, Philip K.; Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The Gender and Social Inclusion (GSI) unit of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is dedicated to the advancement of gender-responsive climate policies. This document is a guide to best practices for developing indicators to track progress toward CCAFS gender-related policy sub-intermediate development outcomes (sub-IDOs) and gender activities at project and national levels. While the primary objective of this guide is to be used as a practical resource for CCAFS projects in tracking progress towards CCAFS gender-related policy sub-IDOs, the methodology and frameworks developed herein would be useful for other programs in selecting which gender issues should be prioritized in climate policy and how these can be instrumentalized in tracking through appropriate and meaningful gender indicators. This guide also provides a synthesis of best practices and recommendations for tracking gender outcomes in climate policy by drawing upon both extant literature and project experiences revealed by CCAFS project leaders and experts (n=14). A discussion of the limitation of gender indicators and how they can be complemented with other tools and methods is also included.